PTH-063 Dietary Advice in an Inflammatory Bowel Disease Clinic – Are We Offering What Patients Want?. (17th August 2016) - Peck, E; Blair, K; Reynolds, N; Mowat, C; Groome, M; Robinson, E
Abstract : Introduction: Inflammatory Bowel Disease (IBD) is a lifelong condition; predominantly diagnosed in young adults, adolescents and children it can also commonly involve malnutrition. The IBD Service Standards suggest all patients should have access to dietary advice, during hospital stays and in out-patients, whether in relapse or remission. We wanted to assess the nature and demand for dietary advice within a cohort of out-patients. Methods: Over a three week period, consecutive patients attending the IBD clinic in a Teaching Hospital were given an anonymised questionnaire. The questionnaire covered individual demographics, history of their condition, whether they had received dietary advice and from whom. Additionally, we asked for their preferred format of dietary advice. This data was analysed according to the relationships between these categories. Results: A total of 136 questionnaires were completed. 80 (59%) were completed by females, aged 20–86 years, and 56 (41%) by males, aged 17–82 years. 78 patients indicated they had Crohn's Disease (CD) (M:F 32:46) and 54 Ulcerative Colitis (UC) (M:F 24:30); 7 marked the field as "unknown". 76% of all patients would like a dietary resource but only 50.7% had received advice previously (58% of patients with CD, and 41% with UC). 50% of those diagnosed in the past year, and 50% who were not, had received dietary advice. The majority of dietary advice was given by a dietician (43%), then a doctor (28%), then friends or from personal research (16%) and finally, IBD nurses gave dietary advice 9% of the time. In 4% the source of advice was unknown. Of those wanting dietary advice the most popular formats were written (35%) followed by no preference and online (both 29%), then electronic (7%). The majority (54%) stated that if a resource was available, they would not need to see a dietician. Conclusion: Half of the patients in this cohort have received no dietary advice despite there being a clear demand for it. Additionally, this figure has not improved in the past year. The majority of patients with CD have had formal dietetic advice and this has mainly been delivered by dieticians, which is appropriate. There remains however a high demand within patients with IBD to receive dietary advice. Patients would be happy to receive advice through an accessible resource rather than see a dietician face to face; this should be available to allow limited dietetic time to be focussed on those patients with a specific need. A written, widely available resource proves to be the best format for this. Disclosure of Interest: None Declared